Sequence Types and Antimicrobial Resistance Profiles of Streptococcus uberis Isolated From Bovine Mastitis - Käppeli, Nadine; Morach, Marina; Zurfluh, Katrin; Corti, Sabrina; Nüesch-Inderbinen, Magdalena; Stephan, Roger (Frontiers in Veterinary Science, 2019)
Bovine mastitis is one of the most common diseases among dairy cows and causes high economic losses in dairy industries worldwide. Streptococcus uberis one of the most frequently identified pathogens causing the disease. In this study, 153 S. uberis strains isolated from mastitis milk samples were analyzed for their genetic diversity using multi locus sequence typing (MLST). Moreover, antibiotic susceptibility testing was performed using a microdilution assay and eleven antimicrobial agents including penicillin, which is the first line agent for treatment of bovine mastitis in Switzerland. MLST was successful for 152 (99.3%) of the strains. Overall, 103 different sequence types (STs) were determined, including 91 novel STs. S. uberis belonging to clonal complex (CC)5 represented 47 (30.7%) of the mastitis cases. Two (1.3%) of the strains belonged to CC86 and one (0.7%) to CC143. The population structure identified in this work suggests that environmental transmission is the predominant route of infection in herds in Switzerland. Antimicrobial susceptibility testing determined a resistance rate of 11.8% for pirlimycin and elevated MIC90-values for marbofloxacin as well as for erythromycin. This study highlights the importance of genetic characterization of S. uberis and the need for veterinary breakpoints for surveillance of antimicrobial resistance in S. uberis.